Effect of COVID-19 on patient access to health services for noncommunicable diseases in Latin America: a perspective from patient advocacy organizations - Meredith H. Kruse; Alessandra Durstine; Dabney P. Evans (BMC, 2022)
Abstract Background The COVID-19 pandemic has been felt acutely in Latin America with several countries having among the highest numbers of SARS-CoV-2 cases and related deaths. Individuals living with underlying health conditions have an increased risk of severe disease or death from COVID-19. Patient advocacy organizations often provide supportive services to these individuals and can offer a unique perspective of the patient experience. The objective of this study was to assess the effects of COVID-19 on access to health services in Latin America, as reported by patient advocacy organizations representing individuals living with autoimmune, chronic, and noncommunicable diseases. Methods A cross-sectional study was conducted in August 2020 with patient advocacy organizations in Latin America to measure perceived effects from COVID-19 and reported access to health services among individuals living with autoimmune, chronic, and noncommunicable diseases. An original, online survey was developed and deployed in Spanish and Portuguese. Univariate and bivariate analysis was conducted across two main subject areas: perceived patient effects from COVID-19 and patient access to health services. The main outcomes of analysis considered patient access to care during COVID-19 based on type of chronic illness and geographical region in Latin America. Results A total of 81 survey responses were analyzed. A majority (83%) of patient advocacy organizations reported their patients experienced delays receiving their treatment and care services; 52% experienced delays of 30 days or more. Telemedicine was considered available, but not accessible to patients (37%) and a majority (76%) of patients faced challenges with electronic prescriptions. Patients were not likely to receive a multi-month prescription from their doctor (38%) or successfully fill it at the pharmacy (26%). Conclusions According to responses from patient advocacy organizations, individuals living with noncommunicable diseases in Latin America have faced unique challenges during the COVID-19 pandemic. As countries re-evaluate their health systems, it is critical that chronic diseases are considered so that all can fully realize the right to health.